(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The article presents the possibilities of using specialized software such as Mathcad, Matlab, Mapl, Matematica in learning algebraic materials, and these possibilities serve to organize lessons effectively and interestingly.